Analisis Perilaku Pedagang dalam Pencegahan Penularan Coronavirus Disease 2019 di Pasar Wameo Kota Baubau - Andriani, Rininta; Islamy, La Ode Syaiful; Amiruddin, Eky Endriana; Sasmita, Sasmita (Rumah Sakit Ibnu Sina, Makassar, 2022)
Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by a newly discovered type of coronavirus. The purpose of this study was to explore in-depth the knowledge, attitudes, and actions of traders in preventing the transmission of Covid-19 at Wameo Market, Baubau City. The type of research used is qualitative with a phenomenological approach. There were 11 informants in this study. The technique of determining the informants is purposive sampling. Primary data collection by conducting interviews and secondary data from Wameo Market Profile. Data analysis is using content analysis. The results of this study indicate that traders already have good knowledge about the meaning, symptoms, and transmission of Covid-19. Traders have a positive attitude regarding the prevention of Covid-19, while for the action aspect, traders are still lacking discipline in wearing masks and maintaining distance. The conclusion of this study is that the behavior of traders related to Covid-19 prevention seen from the aspect of knowledge about the symptoms, transmission, and prevention of Covid-19 is good. Traders have a positive attitude about preventing Covid-19, while some aspects of the action have washed their hands, but for the use of masks and maintaining distance, there is still a lack of discipline. As for the advice in this study, on the contrary, the public is expected to obey the government's advice, especially to use masks when carrying out activities outside the home, especially in public places such as markets, and not crowd and wash hands in order to reduce the risk of transmission of the Covid-19 virus.